2018
DOI: 10.1093/mnrasl/sly023
|View full text |Cite
|
Sign up to set email alerts
|

Direct Lyman continuum and Ly α escape observed at redshift 4

Abstract: We report on the serendipitous discovery of a z = 4.0, M 1500 = −22.20 star-forming galaxy (Ion3) showing copious Lyman continuum (LyC) leakage (∼ 60% escaping), a remarkable multiple peaked Lyα emission, and significant Lyα radiation directly emerging at the resonance frequency. This is the highest redshift confirmed LyC emitter in which the ionising and Lyα radiation possibly share a common ionised channel (with N HI < 10 17.2 cm −2 ). Ion3 is spatially resolved, it shows clear stellar winds signatures like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(223 citation statements)
references
References 48 publications
(53 reference statements)
16
203
3
1
Order By: Relevance
“…Studies have suggested that galaxies with high LyC escape fractions commonly shows strong Lyα emission (EW 0 (Lyα) > 70Å) and high Lyα emission line escape fraction > 20% (e.g., Verhamme et al 2017;Kimm et al 2019). To our knowledge, the Lyα EW 0 in the composite spectrum of these LAEs is higher than all of the known LyC-leaking galaxies with f esc > 30% (e.g., Verhamme et al 2017;Vanzella et al 2016Vanzella et al , 2018 (Figure 4). The other properties of the LAEs in this work are also in favour to having high LyC escape fraction, including lower stellar mass and UV luminosity, compared to those individual galaxies with high LyC escape fraction ( f esc > 30%) at the similar redshift range, such as Ion2, Ion3, and A2218-Flank (Figure 4).…”
Section: Lyc Emission and Galaxy Propertiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Studies have suggested that galaxies with high LyC escape fractions commonly shows strong Lyα emission (EW 0 (Lyα) > 70Å) and high Lyα emission line escape fraction > 20% (e.g., Verhamme et al 2017;Kimm et al 2019). To our knowledge, the Lyα EW 0 in the composite spectrum of these LAEs is higher than all of the known LyC-leaking galaxies with f esc > 30% (e.g., Verhamme et al 2017;Vanzella et al 2016Vanzella et al , 2018 (Figure 4). The other properties of the LAEs in this work are also in favour to having high LyC escape fraction, including lower stellar mass and UV luminosity, compared to those individual galaxies with high LyC escape fraction ( f esc > 30%) at the similar redshift range, such as Ion2, Ion3, and A2218-Flank (Figure 4).…”
Section: Lyc Emission and Galaxy Propertiesmentioning
confidence: 75%
“…However, LyC escape fraction can not be directly measured in galaxies beyond z = 4.5 due to the high opacity of the IGM to LyC ionising photons (e.g., Vanzella et al 2018). Thus we have to infer the LyC escape in the galaxies at the epoch of the reioisation based on either directly measuring LyC escape fraction in galaxies at lower redshift or correlating galaxy spatial positions with the Lyman alpha forest at z > 6 (e.g., Kakiichi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…So, as far as we know, all GCs might have formed inside dwarfs. However, objects similar to the lensed ones found by Vanzella et al (2017a), which have halflight radii of ∼ 60 pc, would be barely resolved with NIRCam.…”
Section: Sizesmentioning
confidence: 86%
“…Thus, for metalpoor GCPs dust extinction is likely to have only a minor effect. It is worth noting in this context that the candidate GCPs detected by Vanzella et al (2017a) have indeed a very blue UV continuum, hence low extinction.…”
Section: Extinctionmentioning
confidence: 91%
See 1 more Smart Citation